ГАСТРОЭЗОФАГЕАЛЬНАЯ РЕФЛЮКСНАЯ БОЛЕЗНЬ: ОСОБЕННОСТИ БАЗИСНОЙ ТЕРАПИИ - Н. Л. Аванян; А. А. Яковлев; Е. В. Мезжуева; С. Н. Халявкин; А. И. Паленый (Архивъ внутренней медицины)
The authors present their own clinical experience in treating elderly patients with gastroesophageal reflux disease using different therapy regimens: monotherapy with proton pump inhibitors (Omeprazole Sandoz) and H2-histamine blockers using a combination of a prokinetic in different modes of observation. It is shown that use of Omeprazole Sandoz is preferable in terms of efficacy, safety and cost of treatment.